Analyzing The Level of Understanding Towards Reading Comprehension Among the Eight Grade Students of MTsN 3 Banda Aceh - Fitrah, Gita; Muliawati, Ida; Fauzan, Fauzan (JETLi: Journal of English Teaching and Linguistics, 2024)
Reading is a very important skill for students to master in learning English because, through reading students can understand what is conveyed in learning and also to increase students' vocabulary. Based on the independent curriculum at school, grade 2 students at MTsN 3 Banda Aceh have studied two aspects, namely detailed information and vocabulary. This research aimed to analyze the level of understanding towards reading comprehension faced by students in reading comprehension by class VIII students at MTsN 3 Banda Aceh. This research design is a descriptive quantitative research design. The population in this studied was the eighth grade at MTsN 3 Banda Aceh with three classes, with a population of 96 students, so the sample taken in this study was 33 students. The sample was selected using simple random sampling technique. To collect data, research can analyze the data using descriptive statistically that can be calculated by Ms. Excel. In addition, students analyzed difficulties in reading comprehension, including: detailed information and finding the meaning of vocabulary. In conclusion, the students of grade VIII of MTsN 3 Banda Aceh have a good understanding of toward the reading comprehension test in the aspects of detailed information and vocabulary meaning questions. It can be seen from the percentage score of the detailed information and the vocabulary meaning that they got 84% and 93,6% respectively. It is because the grade VIII students of MTsN 3 Banda Aceh have studied various vocabulary in the teaching and learning process of English subject, so they can answer the test questions. Reading is a very important skill for students to master in learning English because, through reading students can understand what is conveyed in learning and also to increase students' vocabulary. Based on the independent curriculum at school, grade 2 students at MTsN 3 Banda Aceh have studied two aspects, namely detailed information and vocabulary. This research aimed to analyze the level of understanding towards reading comprehension faced by students in reading comprehension by class VIII students at MTsN 3 Banda Aceh. This research design is a descriptive quantitative research design. The population in this studied was the eighth grade at MTsN 3 Banda Aceh with three classes, with a population of 96 students, so the sample taken in this study was 33 students. The sample was selected using simple random sampling technique. To collect data, research can analyze the data using descriptive statistically that can be calculated by Ms. Excel. In addition, students analyzed difficulties in reading comprehension, including: detailed information and finding the meaning of vocabulary. In conclusion, the students of grade VIII of MTsN 3 Banda Aceh have a good understanding of toward the reading comprehension test in the aspects of detailed information and vocabulary meaning questions. It can be seen from the percentage score of the detailed information and the vocabulary meaning that they got 84% and 93,6% respectively. It is because the grade VIII students of MTsN 3 Banda Aceh have studied various vocabulary in the teaching and learning process of English subject, so they can answer the test questions.